Preliminary study of plant extract on seed germination - Lim, B.-C. (Institute of Physics Publishing, 2020)
The present study was aimed to evaluate the phytotoxic activity of crude leaf extract from Dilleniaceae family on seed germination of goosegrass (E. indica) under different concentrations, ranging from 0-10 mg/mL. The total phenolic content (TPC) was studied and found to be about 209 mg GAE/g extract. Crude extract was significantly inhibitory towards germination of E.indica seeds. Concentration of 10 mg/mL extract demonstrated high germination inhibition rate at 90 of goosegrass seeds as compared to the control. The bioassay results illustrated that the extract markedly inhibited the germination of goosegrass seeds which may require further investigation for the potential use in crop protection. Introduction. Â© Published under licence by IOP Publishing Ltd.